Applying the Spencer-Oatey Model for Investigating the Politeness Strategies in EFL Teacher-Student Interactions (Raparin Journal of Humanities (RJH), 2022)
One of the main goals of learning any language is the ability to communicate, and politeness is considered an important aspect of communication in each language and culture. The main purpose of this study was to investigate politeness strategies that are used in EFL classroom interactions between teachers and students based on the framework of Spencer-Oatey (2008). To this end, students of five EFL classes (N =148) in two cities in Iraqi Kurdistan, Erbil and Sulaimani, were selected and their interactions with teachers (N = 5) were audio-recorded. Transcription of the recorded data revealed that teachers used all the politeness strategies of the Spencer-Oatey model in which equity rights was the most frequent strategy of politeness, while only three strategies of the Spencer-Oatey model were used by the students, which were Identity of Face, Quality of Face, and Equity Rights. Moreover, the results of this study revealed that classrooms in the context of the study are mostly teacher-oriented, teachers manage the classroom, and students mostly speak when they are asked to answer a question. Therefore, it is recommended that teachers attempt further to engage the students and provide situations for more communication.